ANALISIS FAKTOR PENYEBAB KESULITAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SD NEGERI 6 BUMI NABUNG ILIR - Cintia, Riska; Wijaya, Sastra; Rahayu, Maulina (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the factors causing writing difficulties in Indonesian language learning among second-grade students at SDN 6 Bumi Nabung Ilir. The research was motivated by low writing skills, reflected in difficulties forming letters, slow writing speed, and frequent errors in the use of capital and lowercase letters. A descriptive qualitative method was employed with data collected through observation, interviews, and documentation. The subjects were selected using purposive sampling. The findings revealed three main types of writing difficulties: forming letters, writing at appropriate speed, and inaccurate use of capital and lowercase letters. The causes stemmed from internal factors, including weak physical condition, underdeveloped fine motor skills, low motivation and interest, and individual talent differences; and external factors such as limited family support, teacher’s instructional methods, school environment, and the influence of social media. The study recommends more effective, varied, and engaging writing strategies for elementary school students.